Kemampuan Morfosintaksis Anak Disabilitas Intelektual: Studi Kasus - Kumaralalitya Wisnu (Madah: Jurnal Bahasa dan Sastra, 2023)
This case study, whose subject’s initial is KH, was a person with mild intellectual disability which was known from the subject's morphosyntactic abilities. This study used an assessment method to determine KH’s abilities in morphology and syntax when speaking in everyday life. The researcher asked KH to tell her daily activities and to retell them from the available pictures. It can be concluded that KH is capable in making sentences in accordance with sentence elements such as subject, predicate, object, adverb, and conjunction. However, in terms of morphological abilities, KH more often uses predicates in a form of basic word in her uttered sentences instead of affixed verbs which might cause ambiguity of meaning.